How to read church history - Comby, Jean (New York : Crossroad Publishing Company, 1985)
Contents: V.1. From the beginnings to the fifteenth century - V.2. From the Reformation to the present day
Translation of: Pour lire l'histoire de l'Eglise Includes bibliographies
Keywords: Church history; Catholic Church -- History